Aelurostrongylus abstrusus Infections in Domestic Cats (Felis silvestris catus) from Antioquia, Colombia - Sara Lopez-Osorio; Jeffer Leonardo Navarro-Ruiz; Astrid Rave; Anja Taubert; Carlos Hermosilla; Jenny J. Chaparro-Gutierrez (Pathogens, 2021)
Although Aelurostrongylus abstrusus infections in domestic cats (Felis silvestris catus) have sporadically been reported in Colombia, there is still no data available on epidemiology nor on the biology of this neglected lungworm parasite. Thus, this epidemiological study aimed to evaluate the occurrence of patent A. abstrusus infections in domestic cats from the Colombian Federal State of Antioquia. In total, 473 fecal samples of indoor/outdoor domestic cats were collected and analyzed thereafter by the Baermann funnel migration technique for the presence of A. abstrusus first stage larvae 1 (L1). The occurrence of A. abstrusus was confirmed in 0.4% (2/473) of investigated cats. Due to the presence of patent A. abstrusus infections in investigated cats, it is unfailing to include this lungworm within differential diagnoses of feline pulmonary disorders. Despite the fact that the Baermann funnel technique is currently the cheapest and the gold standard diagnostic tool for feline aelurostrongylosis, this technique is still unknown by Colombian veterinary surgeons and rarely utilized in small animal veterinary clinics. The current survey intends to generate awareness on this neglected parasitosis and to be considered as a baseline study for future surveys monitoring feline aelurostrongylosis not only in domestic/stray cats but also in endemic wild felid species of Colombia.